Hospital at Home in an oncology setting: Updated analysis. Issue 28 (1st October 2022) - Kier, Melanie Wain; Lubetsky, Sara; Schiller, Gabrielle; Siu, Albert L.; Ornstein, Katherine A.; Smith, Cardinale B.
Abstract : 257 Background: Hospitalization at Home (HaH) is an emerging clinical model that delivers the essential elements of acute hospital-level care in the home and has demonstrated efficacy largely for inpatient medical conditions. Few programs have implemented HaH for patients with active cancer diagnoses. There is little data evaluating the impact of HaH on cancer outcomes, patient experience or cost effectiveness. In 2019, the Mount Sinai Health System (MSHS) expanded its HaH program to include oncology patients. Here, we describe our institution's experience of HaH in oncology as we continue to increase enrollment. Methods: We performed a retrospective chart review for solid tumor, myeloma and lymphoma patients at MSHS from August 2019 to April 2022 enrolled in HaH. Our updated analysis includes additional patients from what was previously presented at ASCO Annual Meeting June 2022. Patient eligibility for HaH required meeting established institutional HaH admission criteria. Demographics, cancer diagnosis, social situation, indication for antecedent ED or inpatient stay, and HaH admission were extracted from the electronic medical record. Our primary endpoint was rate of successful HaH admission, with success defined as discharge from HaH for complete recovery from the acute condition or transition to hospice. We also evaluated patient social support and home resources. Results: We enrolled 27 patients with multiple myeloma (n = 13), lymphoma (n = 1), and solid tumor (n = 13), which is an additional 8 patients from the data presented prior. Sixty-three percent (n = 17) were male, 67% (n = 18) were age 65 or older, and 33% (n = 9) were white. Patients were enrolled in HaH either from an inpatient service (n = 21) or from the emergency room (n = 6). While on the inpatient service, 12 of the 21 patients had received chemotherapy. Post-chemotherapy monitoring was the primary reason for HaH admission. Successful HaH admissions occurred for 85% (n = 23) of patients. The mean duration of HaH admission was 5.6 days (range 1-13 days). Four patients opted to re-enroll in HaH planned care at a later point. There were no significant issues with provider home visits, access, medication delivery, lab draws, or social support. Conclusions: The MSHS Oncology HaH program successfully cared for 85% of our cohort demonstrating the functionality of expanding the program to patients with cancer. We continue to increase enrollment and develop clinical pathways available on hospital at home for our oncology patients.